2010
DOI: 10.1027/1614-0001/a000010
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Tests, Familiarity with the Surroundings, and Spatial Activity Experience

Abstract: Spatial orientation as the ability to know the bearing to the origin of a walked path was investigated in two studies with ca. 140 preschool and primary school children who walked paths of about 1 km beginning at the familiar kindergarten or in a completely unknown territory. Path difficulty and familiarity with the surroundings influenced correctness of pointing. Spatial ability measured by test performance and spatial activity experience, i.e., children’s reports about unsupervised walks, effected pointing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 20 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…This perceptual test requires the ability to judge directions, distances and angles, but also to represent an imaginary line. Such abilities are also required for large-scale pointing, often used to measure wayfinding capacities (e.g., Neidhardt and Popp, 2010 ). Quaiser-Pohl et al (2004) studied the relationship between spatial abilities and spatial representation of a large-scale environment in second-, fourth-, and sixth- graders.…”
Section: Discussionmentioning
confidence: 99%
“…This perceptual test requires the ability to judge directions, distances and angles, but also to represent an imaginary line. Such abilities are also required for large-scale pointing, often used to measure wayfinding capacities (e.g., Neidhardt and Popp, 2010 ). Quaiser-Pohl et al (2004) studied the relationship between spatial abilities and spatial representation of a large-scale environment in second-, fourth-, and sixth- graders.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other authors have suggested that the differences are the result of experience and the differential participation of male and female children in activities, combined with hormonal changes during puberty (Jordan & Wüstenberg, 2010;Roberts & Bell, 2002). Support for the latter hypothesis is provided by recent studies showing that mental rotation performance can be enhanced with practice, and that these enhancements are sex-specific (Feng, Spence, & Pratt, 2007;Neidhardt & Popp, 2010;Quaiser-Pohl & Lehmann, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Several papers focus on the development of spatial abilities in childhood : Which task, person, and environmental factors predict how well children are oriented in real environments (Neidhardt & Popp)? How does the ability to use maps develop ontogenetically, and how can proficiency in map use be measured (Peter, Glück, & Beiglböck)?…”
mentioning
confidence: 99%